2010
DOI: 10.1111/j.1365-2222.2009.03361.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of iodine in hypersensitivity reactions to radio contrast media

Abstract: We have previously demonstrated in patients with iodine mumps that an oral challenge with LS is a valid means to elicit hypersensitivity reactions to iodine. In 19 patients, we showed that iodine is rarely the eliciting agent in hypersensitivity reactions to RCM. Only one patient with a late urticaria to an RCM with a late urticaria to LS and two patients with DT and broad sensitization to all RCM tested reacted to LS with an exanthema. In most cases, more likely the RCM molecules and not iodine are the elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 30 publications
1
24
0
5
Order By: Relevance
“…7,20,21 In the present study, the 7 allergic history-free patients out of the 375 ADR patients were found with obvious anxiety, nervousness and fear before the examination, and vasovagal symptoms including palpitation or shortness of breath during the examination, which we believed could be largely associated with poor psychological factors. Therefore, technicians and nurses in the CT room should better communicate with patients, provide sufficient health education, comfort and encourage patients with anxiety, nervousness and fear, and help patients to complete the examination.…”
Section: Discussionmentioning
confidence: 87%
“…7,20,21 In the present study, the 7 allergic history-free patients out of the 375 ADR patients were found with obvious anxiety, nervousness and fear before the examination, and vasovagal symptoms including palpitation or shortness of breath during the examination, which we believed could be largely associated with poor psychological factors. Therefore, technicians and nurses in the CT room should better communicate with patients, provide sufficient health education, comfort and encourage patients with anxiety, nervousness and fear, and help patients to complete the examination.…”
Section: Discussionmentioning
confidence: 87%
“…We consider that the benefit of avoiding allergic reactions outweighs the possible improvement in visibility. 9,25,26 Instead, in order to reduce the risk of hypoparathyroidism we perform parathyroid re-implantation where these are seen to be devascularized at the time of surgery. Parathyroid reimplantation has been shown to decrease the rate of hypoparathyroidism as a complication.…”
Section: Discussionmentioning
confidence: 98%
“…44 Cutaneous delayed reactions are thought to be due to a T-cell-mediated type IV hypersensitivity reaction and are believed to be a reaction generated against the ICA molecule itself, not iodine. 45 Delayed reactions are more common in patients treated with interleukin 2 because interleukin 2 is a potent stimulator of T lymphocytes. 46 As with acute reactions, the management goal for delayed reactions is to identify patients at risk and minimize the risk of a reaction.…”
Section: Delayed Reactions To Contrast Agentsmentioning
confidence: 99%